2010
DOI: 10.1155/2010/170819
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Hydrogen + Tetra-n-Butyl Ammonium Bromide Semi-Clathrate Hydrate

Abstract: Thermodynamic stability and hydrogen occupancy on the hydrogen + tetra-n-butyl ammonium bromide semi-clathrate hydrate were investigated by means of Raman spectroscopic and phase equilibrium measurements under the three-phase equilibrium condition. The structure of mixed gas hydrates changes from tetragonal to another structure around 95 MPa and 292 K depending on surrounding hydrogen fugacity. The occupied amount of hydrogen in the semi-clathrate hydrate increases significantly associated with the structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…Table 1 lists the experimental hydrate dissociation data reported in the literature for the hydrogen +water and hydrogen+ TBAB+ water systems, as mentioned earlier. We used the experimental data reported by Mao and Mao (Mao and Mao, 2004) for the hydrogen +water system and Hashimoto et al (2006Hashimoto et al ( , 2008Hashimoto et al ( , 2010 and Arjmandi et al (2007) for the hydrogen+ TBAB+ water system to develop our algorithm. These data are shown in Fig.…”
Section: Feed-forward Neural Network Algorithmmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 lists the experimental hydrate dissociation data reported in the literature for the hydrogen +water and hydrogen+ TBAB+ water systems, as mentioned earlier. We used the experimental data reported by Mao and Mao (Mao and Mao, 2004) for the hydrogen +water system and Hashimoto et al (2006Hashimoto et al ( , 2008Hashimoto et al ( , 2010 and Arjmandi et al (2007) for the hydrogen+ TBAB+ water system to develop our algorithm. These data are shown in Fig.…”
Section: Feed-forward Neural Network Algorithmmentioning
confidence: 99%
“…Hydrogen can form gas hydrates at low temperatures and extremely high pressures (Sloan and Koh, 2008;Mao and Mao, 2004;Lokshin et al, 2004;Dyadin et al, 1973Dyadin et al, , 1999. It has been shown that the addition of tetra-n-butyl ammonium bromide (TBAB) in aqueous solution can reduce the pressure required for hydrogen hydrate formation (Hashimoto et al, 2006(Hashimoto et al, , 2008(Hashimoto et al, , 2010Arjmandi et al, 2007). TBAB is a quaternary ammonium salt with a bromine counter ion commonly used as a semi-clathrate hydrate promoter.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of aqueous TBAB solutions results in differences of the crystal structure and thermodynamic stability of TBAB hydrate. TBAB semiclathrate hydrates have become the subject of much attention as an attractive medium for not only refrigerant but also H 2 storage [7][8][9].…”
Section: Introductionmentioning
confidence: 99%